2017
DOI: 10.1002/bmc.3962
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of antofloxacin and its major metabolite in human urine by HPLC–MS/MS, and its application to a pharmacokinetic study

Abstract: This study presents a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method for the simultaneous determination of antofloxacinin and its main metabolite - N-demethylated metabolite (N-DM) - in human urine. Ornidazole was used as the internal standard. This was a clinical urine recovery study, in which 10 healthy Chinese volunteers were intravenously administered a single 200 mg dose of antofloxacin hydrochloride. Compounds were extracted by albumen precipitation, after which sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, it remains a common practice to prescribe fluoroquinolones, such as levofloxacin, norfloxacin, and ciprofloxacin, for the treatment of urinary tract infections (9). Indeed, in vitro resistance would not be expected to predict the clinical outcomes of urinary tract infections since urine antimicrobial levels are generally significantly higher than serum levels for most fluoroquinolones (13,15). For cystitis, the microbiological endpoints can frequently be achieved, despite the in vitro resistance of the uropathogens to fluoroquinolones (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains a common practice to prescribe fluoroquinolones, such as levofloxacin, norfloxacin, and ciprofloxacin, for the treatment of urinary tract infections (9). Indeed, in vitro resistance would not be expected to predict the clinical outcomes of urinary tract infections since urine antimicrobial levels are generally significantly higher than serum levels for most fluoroquinolones (13,15). For cystitis, the microbiological endpoints can frequently be achieved, despite the in vitro resistance of the uropathogens to fluoroquinolones (31).…”
Section: Discussionmentioning
confidence: 99%
“…Antofloxacin is a novel levofloxacin derivative approved by the China Food and Drug Administration (CFDA) for the treatment of acute uncomplicated cystitis and AP due to E. coli (12). This drug targets the urinary tract, judging from the high urine drug concentrations (13). The results of urine antofloxacin assays indicated that 40 to 45% of the parent drug is excreted in the urine by 72 h after administration (14).…”
mentioning
confidence: 99%
“…As a representative derivative of fluoroquinolones (floxacins), antofloxacin hydrochloride (C 18 H 22 ClFN 4 O 4 , CAS Registry Number 873888-67-6, molecular structure shown in Figure ) has a broad-spectrum antibacterial activity prominently in vitro and in vivo compared to other fluoroquinolones, i.e., ciprofloxacin, ofloxacin, and sparfloxacin due to the introduction of 8-position NH 2 based on antibiotic levofloxacin. It was first developed as a brand-new fluoroquinolone antibiotic for the treatment of respiratory tract and urinary tract infection in China. Literature survey show that antofloxacin hydrochloride exhibited good rapid absorption and oral bioavailability, broad tissue distribution, no fluoroquinolone-related toxicity, and a long elimination half-life in both animal and humans according to some clinical pharmacokinetic studies. ,,− Refs , reported using 8-aminolevofluorocarboxylic acid, N -methyl piperazine, and pyridine as raw materials to synthesize antofloxacin and then reacting with hydrochloric acid to obtain antofloxacin hydrochloride product.…”
Section: Introductionmentioning
confidence: 99%